2019
DOI: 10.5114/aoms.2017.68528
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzyme expression of mRNA and protein in the epididymis of finasteride-treated male rat offspring during postnatal development

Abstract: A b s t r a c tIntroduction: We verify whether finasteride had a transgenerational effect on the epididymal expression of antioxidant enzymes, and the correlation between these enzymes and blood androgen concentrations in male offspring (F1:Fin) of females fertilized by finasteride-treated male rats. Material and methods: The expression of CAT, SOD1, GPX5, GR on the mRNA and protein levels was evaluated in the epididymis at postnatal day (PND) 7, 14, 21, 28 and 90. Levels of T and DHT were correlated with mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 89 publications
(123 reference statements)
2
11
0
Order By: Relevance
“…In our previous reports [ 32 , 33 ] conducting on the same experimental model we showed that, the male rats from F1:Fin group were characterized by a differing serum testosterone and dihydrotestosterone concentration in comparison to the F1:Control.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…In our previous reports [ 32 , 33 ] conducting on the same experimental model we showed that, the male rats from F1:Fin group were characterized by a differing serum testosterone and dihydrotestosterone concentration in comparison to the F1:Control.…”
Section: Resultsmentioning
confidence: 76%
“…However this mechanism will be in the future evaluated by us (see Appendix A ). The observed overweight could have been also associated with the modulation of adipose tissue metabolism by androgens (mainly DHT), as indicated by microarrays analysis by Zhang et al [ 45 ], and therefore could be the result of a changed T–DHT ratio [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations